ANALISIS HUBUNGAN ANTARA KEPUASAN KERJA DAN MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN SURVEI DI KOPERASI BEN MAKMUR, MUARA TAWAR, BEKASI - Haryadi Haryadi (Universitas Bunda Mulia, 2017)
The purpose of this study was to find out whether there is a relationship and how strong the relationship between job satisfaction and achievers motivation. This study uses survey methods, sampling research was carried out by means of a stratified random sampling. From a population of 126 people were chosen as much as 120 people as respondents, in accordance with the Slovin formula; with details of 32 people involved to test the instrument, while the remaining research 88 people as samples in the collection of research data, selected by simple random sampling. Based on the conclusion of the research results can be said that employees performance can be enhanced through efforts to increase job satisfaction and increased achievers motivation. Increased job satisfaction can be done with decent wages policy, any chance of promotion as a fair, equitable and tranparent, congruency between tasks and interests of workers and there are awards to workers who are achievers.Increase the achievers motivation can be done with any hope of a better future, there is justice in the working environment, there is a sense like accept responsibility, there is a sense of love to receive feedback and orientation on the achievement of goals. In this study only examined the limited influence of the job satisfaction and achievers motivation for the employees performance.Key Words- Job satisfaction, achievers motivation and employees performance.